SISTEM INFORMASI PROGRAM KREATIVITAS MAHASISWA BERBASIS WEB SERVICE DAN MICROSERVICE - Lokapitasari Belluano, Poetri Lestari; Purnawansyah, Purnawansyah; Panggabean, Benny Leonard Enrico; Herman, Herman (ILKOM Jurnal Ilmiah, 2020)
The information system is faced with a significant development, it needs to have not only the policy changes but also the features as an effort update, according to necessity both internal and external business rule systems. This research aims to form a microservice infrastructure for updating changes in flow of business process to the development of information systems. This Research methods come under both field studies and literature to the subject matter related with the development of Information Systems in managing data of program kreativitas mahasiswa (PKM), Web services and Microservice Architecture. The design is using Prototype model to represent graphically the workflow of the system Model which is using the Unified Modeling Language (UML) tool, Managing the Data Base Management System (DBMS) application using GORM, Go Validator as a data validation tool, and Gorilla Mux as the REST rooter. The application runs by utilizing the Advanced Message Queuing protocol. In conclusion, the implementation of webservice-based university internal information system development with microservice architecture for PKM is reporting activities in where the relationship between units in data transactions (publish, send automatically) is carried out with a duration of time 0,00 / sec.